Livestock and poultry slaughter leftover fodder for crabs and preparation method of fodder - ZHANG HOUBING (2014)
The invention discloses a livestock and poultry slaughter leftover fodder for crabs. The fodder is characterized by being prepared from the following raw materials by weight: 1-2 parts of butyl hydroxy anisol, 3-6 parts of vanilla spicy oil, 2-4 parts of zinc oxide, 13-15 parts of potash feldspar, 19-24 parts of rice bran, 25-30 parts of bean pulp, 13-16 parts of sea sedge, 23-28 parts of goat bone, 24-32 parts of livestock and poultry slaughter leftovers, 1-3 parts of five spice powders, 17-19 parts of eggs, 4-7 parts of garlic, 2-4 parts of salt, 14-18 parts of purple cabbage, 15-18 parts of sea lettuce, 17-21 parts of shepherd's purse, 0.3-0.5 part of poria cocos, 0.6-1.2 parts of dried orange peel, 0.3-0.7 part of juncus effusus, 3-6 parts of phagostimulants and a proper amount of water. The fodder effectively solves the problems of the excessive protein level of the compound fodder and the serious environment pollution during the crab breeding process nowadays, improves the profit of enterprises, reduces